KONSEP PENDIDIKAN ISLAM MENURUT IKHW?N AL-SHAF? - Hairus Sodik; Moh. Zainol Kamal (JURNAL PUSAKA, 2018)
Ikhw?n al-Shaf? is an organization founded by a community that consisting of Muslim philosophers. This organization focused on da'wah and education. It developed at the end of the second Hijriyah in the Basrah city, Iraq. It is a discussion and teaching forum. In general, this emergence is motivated by concerns about the implementation of Islamic teachings that have been tainted by teachings from outside Islam at the time, and to reawaken a love for Islamic science. This organization views education with a rational and empirical view, or a combination of intellectual and factual views. This organization views science as a decribtion of something that can be known and experienced, knowledge produced by human thought that occurs because they get information sent by the five senses and then become developed knowledge.